Leverage over the firm life cycle, firm growth, and aggregate fluctuations - Emin Murat Dinlersoz; Sebnem Kalemli-Ozcan; Henry R. Hyatt; Veronika Penciakova (Federal Reserve Bank of Atlanta, 2019)
We study the leverage of U.S. firms over their life cycles and the connection between firm leverage, firm growth, and aggregate shocks. We construct a new dataset that combines private and public firms' balance sheets with firm-level data from U.S. Census Bureau's Longitudinal Business Database for the period 2005-12. Public and private firms exhibit different leverage dynamics over their life cycles. Firm age and size are systematically related to leverage for private firms but not for public firms. We show that private firms, but not public ones, deleveraged during the Great Recession and that this deleveraging is associated with a reduction in firm revenue and employment growth. Exploiting sectoral variation, we find that the leverage dynamics of firms is also relevant for aggregate fluctuations.
Keywords: E23; G32; 330; leverage; firm dynamics; firm growth; firm life-cycle; financial constraints; borrowing limits; short-term debt; aggregate shocks